Notch Signaling Regulates Lgr5+ Olfactory Epithelium Progenitor/Stem Cell Turnover and Mediates Recovery of Lesioned Olfactory Epithelium in Mouse Model. (8th May 2018) - Dai, Qi; Duan, Chen; Ren, Wenwen; Li, Fangqi; Zheng, Qian; Wang, Li; Li, Wenyan; Lu, Xiaoling; Ni, Wenli; Zhang, Yanping; Chen, Yan; Wen, Tieqiao; et al.
Abstract : The Notch signaling pathway regulates stem cell proliferation and differentiation in multiple tissues and organs, and is required for tissue maintenance. However, the role of Notch in regulation of olfactory epithelium (OE) progenitor/stem cells to maintain tissue function is still not clear. A recent study reported that leucine-rich repeat-containing G-protein-coupled receptor 5 ( Lgr5 ) is expressed in globose basal cells (GBCs) localized in OE. Through lineage tracing in vivo, we found that Lgr5 + cells act as progenitor/stem cells in OE. The generation of daughter cells from Lgr5 + progenitor/stem cells is delicately regulated by the Notch signaling pathway, which not only controls the proliferation of Lgr5 + cells and their immediate progenies but also affects their subsequent terminal differentiation. In conditionally cultured OE organoids in vitro, inhibition of Notch signaling promotes neuronal differentiation. Besides, OE lesion through methimazole administration in mice induces generation of more Notch1 + cells in the horizontal basal cell (HBC) layer, and organoids derived from lesioned OE possesses more proliferative Notch1 + HBCs. In summary, we concluded that Notch signaling regulates Lgr5 + GBCs by controlling cellular proliferation and differentiation as well as maintaining epithelial cell homeostasis in normal OE. Meanwhile, Notch1 also marks HBCs in lesioned OE and Notch1 + HBCs are transiently present in OE after injury. This implies that Notch1 + cells in OE may have dual roles, functioning as GBCs in early development of OE and HBCs in restoring the lesioned OE. Abstract : Notch signaling regulates proliferation and differentiation of Lgr5 + olfactory epithelium basal cells. (A): Notch1 marks Lgr5+ basal cells in olfactory epithelium (OE). (B): Notch activation in vivo enhances proliferation. (C): Notch activation keeps more cells at progenitor and immature state as well as induces generation of more supporting cells and less mature sensory neurons. (D, E): Notch inhibition by DAPT treatment promotes generation of Tuj1+ neuronal cells and decreases the number of p63+ cells in OE organoids compared with that in DMSO control. (F, G): DAPT treatment decreases ratio of Ki67+ proliferative cells and increases OMP+ mature sensory neurons in OE organoids. (H, I): Lesion leads to more Notch1+ICAM1+ horizontal basal cells in OE. (J): OE organoids express Lgr5-mRNA. (K): Organoids from lesioned epithelium contains more Notch1+ cells. (L): More Notch1+ICAM+Ki67+ proliferative horizontal basal cells are generated in organoids from lesioned epithelium.